EXPLORING SUPPORTING FACTORS TO ENHANCE PRE-SERVICE TEACHERS' WELL BEING DURING PRACTICUM PROGRAM - Sahril, Mohamad; Maghfiroh, Rachel Aghny; Rahmawati, Movi Riana (LPPM STISIPOL Mujahiddin, 2025)
Pre-service teachers face both professional growth and emotional challenges during their practicum, making well-being a critical component of their development. This study aims to explore the supporting factors that enhance the well-being of pre-service English teachers during their teaching practicum program. Employing a qualitative case study approach, data were gathered from ten participants through close-ended questionnaires and semi-structured interviews. The findings revealed three main contributing factors to well-being: motivation, student engagement, and appreciation of the teaching profession. Motivation was reinforced by hands-on teaching experiences, while positive student responses and academic progress strengthened emotional satisfaction. Additionally, feeling appreciated—especially by students—boosted pre-service teachers' confidence and professional identity. These factors played a significant role in increasing resilience, fostering commitment, and enhancing the overall teaching experience. The study emphasizes the importance of nurturing these elements to support the psychological and emotional well-being of pre-service teachers, ultimately contributing to their long-term success in the profession.